Reconsidering The Impact of Environment on Long-Run Growth When Pollution Influences Health and Agents Have Finite-Lifetime - Xavier Pautrel (Fondazione Eni Enrico Mattei (FEEM), 2006)
Using an overlapping generation model à la Blanchard (1985) with human capital accumulation, this article demonstrates that the influence of environment on optimal growth in the long-run may be explained by the detrimental effect of pollution on life expectancy. It also shows that, in such a case, greener preferences are growth- and welfare-improving even if the ability of the agents to learn is independent to pollution and utility is additively separable. Finally, it establishes that it is possible to implement a win-win environmental policy.
Keywords: E62; I21; O41; Q28; 330; Growth; Environment; Overlapping Generations; Human Capital; Health; Overlapping Generations; Bildungsinvestition; Umweltbelastung; Gesundheitsrisiko; Sterblichkeit; Theorie